Governance of Innovation and Intermediation in Triple Helix Interactions. (August 2013) - Todeva, Emanuela
Research on sustainability and innovation-driven economic growth has exposed a lack of sufficient knowledge in the governance literature about the appropriate extent of government involvement. This paper focuses on the governance of innovation and the intermediary role of the state. The author synthesizes the literature on governance and regulation and introduces the concept of intermediation in the innovation process. The paper employs the Triple Helix model, which describes interactions and intermediation between government, industry and universities, and extends it by looking at the role played by intermediaries, including public and private institutions, government bodies and independent organizations. A new theoretical framework for the analysis of intermediation and the governance of innovation is developed and applied to four case studies of intermediaries in the health technology cluster in the Greater South East region of the UK. The empirical findings demonstrate the heuristics of the intermediation concept and the application of the intermediation framework.